Drivers of Spatiotemporal Eukaryote Plankton Distribution in a Trans-Basin Water Transfer Canal in China - Li, Yuying; Khan, Faisal Hayat; Wu, Jiamin; Zhang, Yun; Jiang, Yeqing; Chen, Xiaonuo; Yao, Yinlei; Pan, Yangdong; Han, Xuemei (Frontiers in Ecology and Evolution, 2022)
Planktonic eukaryotes are important components of aquatic ecosystems, and the analysis of their community composition and function have far-reaching significance for the water resource management. To understand the spatio-temporal distribution of planktonic eukaryotes community and the drivers in the canal of the Middle Route Project of the South-to-North Water Diversion in Henan Province, China, we examined both planktonic eukaryote assemblages and water quality in five stations along the canal and one station before the dam in march, June, September and December in 2019. High-throughput sequencing results showed that the community of eukaryotic plankton was mainly composed of 53 phyla, 200 genera and 277 species, including Cryptomonadales, Ciliophora, Kathablepharidae and norank_k_Cryptophyceae, etc.. Oxidation-reduction potential (ORP), nitrate nitrogen, pH, total phosphorus and flow velocity were important factors affecting the distribution of eukaryotic plankton through Redundancy Analysis (RDA) on eukaryotic community and environmental factors. The distance-attenuation analysis indicated that the geographical distribution of eukaryotic communities accorded with the distance-attenuation model, and the environmental selection was the dominant driving factor for the geographical distribution of eukaryotic communities. The results of this study complement the lack of knowledge about the diversity and ecological distribution of planktonic eukaryotes in trans-basin diversion channels, and contribute to the understanding of the ecological response of planktonic eukaryotes in trans-basin diversion projects.